Simulation Research of Engaging Process of Clutch based on ADAMS - Liu Xiaochu; Chen Youcheng; Jiang Yin; Cao Jie; Chen Ningbo (Jixie chuandong)
Based on the structure and movement theory of automobile clutch,combined with a clutch structural parameters of a vehicle,a virtual prototype of clutch is built in ADAMS virtual environment platform,and the simulation analysis of the working process of the clutch is carried out,such as ride comfort,impact strength,friction work,etc. Some reference basis for clutch virtual prototype design,simulation and testing is provided.